FRANCO, José Eduardo (1999). Brotar Educação – História da Brotéria e da Evolução do seu Pensamento Pedagógico (1902-1996). Lisboa: Roma Editora, 498 pp - Manso, Artur (Revista Portuguesa de Educação, 2018)
.